Multiple Cranial Neuropathies Caused by Lymphoma-Associated Central Nervous System Involvement in an Immunodeficiency Virus Patient - Sumonthip Leelawai; Pat Korathanakhun (Journal of Health Science and Medical Research (JHSMR), 2020)
Human immunodeficiency virus (HIV) infections increase the risk of malignant lymphoma. Although, lymphoma is a rare cause of central nervous system involvement, it can present as an initial HIV symptom. We report the case of a 35-year-old HIV patient who developed multiple cranial neuropathies. He was diagnosed with diffuse large B-cell lymphoma with meningeal metastasis.